Tepa Selira – Based Career Guidance As An Innovation in Growing Self Compassion of Basic learners in The Digital Era - Farida Farida; Mungin Eddy Wibowo; Edy Purwanto; Sunawan Sunawan (International Conference on Science, Education, and Technology, 2022)
Abstract. One of the problems of basic learner in the digital era is the lack of self acceptance as the result of digital technology development. This conditions require innovative career guidance in assisting basic learners to undergo and design careers for educational levels and job opportunities that suitable to their own conditions. This research used qualitative research method. Meanwhile, data collection techniques are carried out through observation, interviews, and documentation. Data were analyzed using Miles and Huberman pattern, including data reduction, data display, then drawing conclusion. The results of this research are : (1) Tepo seliro - based career guidance as an innovation in growing self-compassion for basic learners of the digital era by provide career information that suitable to personal conditions, family career background as a personal approach, and recognize individual differences in career choice; (2) The supporting factors of Tepo seliro - based career guidance consist of both manual and digital information and examples that are accessed by basic learners of the digital era, the success story of public figures that are easily accessible, and popular targets. Meanwhile, the obstacle factors consisit of desire that does not measure ability, ambition without steps to achieve achievement, result-oriented social demands. The importance of research is to find innovations for growing self-compassion through tepa-selira based career guidance for basic learners of the digital era.